195 Can age be considered as prognostic factor of survival in patients with uterine cervical cancer?. (18th September 2019) - Moschen, H; Mendez, M; Soderini, A; Aragona, A; Bustos, J; Amestica, G; Retamozo, J
Abstract : Objectives: To assess the impact of age as a determining prognostic factor in the survival of women with uterine cervical cancer (UCC). Methods: A retrospective observational study was carried out in which patients who consulted in Oncological Hospital of Buenos Aires, in the period between January 2007 and December 2011. The variables were studied: age and tumor stage. Three age groups were established: patients <35, 35 - 59, and >60. For the analysis of disease-free survival (DFS) and overall survival (OS), the Kaplan-Meier method was used and for the comparison between the different groups, the Log Rank test method using the statistical package IBM Statics Version 21. A statistically significant P value of ≤0.05 was considered. Results: 748 patients were included, of which 145 (19.4%) <35 years, 484 (64.7%) to the group of 35 to 59 years and 119 (15.9%) to >60 years. The median general age was 46 years. The general OS was 59.3% (P=0.04), 48.3%, 63.3% and 57.4% respectively in the groups. The general DFS was 55.5% (P=0.04), in the groups: 45.8%, 59% and 53.6% respectively. The distribution by stages was predominantly locally advanced: IIB 30.6% (229), IIIB 29.5% (221), being statistically significant for OS stages IB2, IIA2, IIB, IIIA and IVA. Conclusions: In addition to the widely known prognostic factors, age also seems to be an important factor, although probably underestimated by current treatment guidelines. There is a population of patients with UCC whose diagnosis at an early age implies an alarming prognosis.